CFA program curriculum. Level III 2010 - CFA Institute.&#x0009 (New York ; CFA Institute/Custom Publishing, 2010)
The Level III study program emphasizes portfolio management and includes strategies for applying the tools, inputs, and asset valuation models in managing equity, fixed income, and derivative investments for individuals and institutions.
v. 1. Ethical and professional standards : study sessions 1-2 --v. 2. Portfolio management : study sessions 3-5 --v. 3. Portfolio management : study sessions 6-8 --v. 4. Portfolio management : study sessions 9-12 --v. 5. Portfolio management : study sessions 13-15 --v. 6. Portfolio management : study sessions 16-18.
Includes bibliographical references and indexes.
lje 9/9/13
Loan
Keywords: Investment analysis -- Examinations -- Study guides; Portfolio management -- Examinations -- Study guides; Securities -- Examinations -- Study guides